Bis(imino)pyrazine-supported iron complexes: ligand-based redox chemistry, dearomatization, and reversible C-C bond formation - Regenauer, Nicolas I.; Settele, Simon; Wadepohl, Hubert; Roşca, Dragoş-Adrian (Inorganic chemistry, 2020)
Iron complexes supported by novel π-acidic bis(imino)pyrazine (PPzDI) ligands can be functionalized at the nonligated nitrogen atom, and this has a marked effect on the redox properties of the resulting complexes. Dearomatization is observed in the presence of cobaltocene, which reversibly reduces the pyrazine core and not the imine functionality, as observed in the case of the pyridinediimine-ligated iron analogues. The resulting ligand-based radical is prone to dimerization through the formation of a long carbon-carbon bond, which can be subsequently cleaved under mild oxidative conditions.